Hubungan Berat Bayi Lahir Rendah (BBLR), Prematuritas, dan Ketuban Pecah Dini (KPD) dengan Kejadian Asfiksia Neonatorum di RSUD Kota Mataram Tahun 2022 - Dwi Arini Oktafianingsih, Berlian; Benvenuto, Ananta Fittonia; Zulhijjah, Nurkomariah; Hanafi, Fachrudi (Peneliti.net, 2024)
Establishment: Asphyxia neonatorum may be a condition where the newborn child comes up brief to breathe all of a sudden and routinely at birth or a couple of time after birth. Inside the world, each year around 3% (3.6 million) of 120 million newborn child babies inclusion asphyxia, about 1 million babies pass on since of it. In Indonesia, the rate of asphyxia is generally 40 per 1000 live births, and in common 110,000 neonates kick the bucket each year due to asphyxia. Asphyxia in NTB Region is the minute most common cause of neonatorum passing after LBW. This explore focuses to choose the relationship between moo birth weight, carelessness and inopportune split of layers with the recurrence of neonatorum asphyxia at Mataram Common Clinic in 2022. Techniques: The ask around arrange is utilized observational analytics with a case control think approximately desain. The analyzing strategy was by purposive testing strategy and a test of 220 tests was gotten. The data source is assistant data from the patient's therapeutic records. The data gotten were analyzed utilizing the Chi-Square relationship test with a significance regard compel (p-value < 0.05). Result: Based on univariate examination, it was found that 50% of babies experienced asphyxia, 50% of babies did not experience asphyxia, and it was found that the larger part of babies were not LBW as much as 71.4%, not inopportune as much as 67.3%, and not PROM as much as 66.4%. Inside the bivariate examination, the relationship between LBW and asphyxia was found (p-value: 0.000, OR: 9.298, 95%CI: 4.392-19.684), the relationship between carelessness and asphyxia (p-value: 0.000, OR: 5.471, 95%CI: 2.891- 10.353) and the relationship between inopportune burst of movies and asphyxia (p-value: 0.001, OR: 2.731, 95%CI: 1.524-4.894). Conclusion: There's a essential corelation between moo birth weight, carelessness, and less than ideal break of movies with rate of neonatorum asphyxia at Mataram Common Clinic in 2022.